2019
DOI: 10.18632/aging.102011
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MEG3 promotes fibrosis and inflammatory response in diabetic nephropathy via miR-181a/Egr-1/TLR4 axis

Abstract: Long non-coding RNAs (lncRNAs) play vital roles in diabetic nephropathy (DN). This research aimed to study the potential role and underlying molecular mechanisms of long non-coding RNA MEG3 in DN. We found that MEG3 was upregulated in DN in vivo and in vitro and could enhance cell fibrosis and inflammatory response in DN. MEG3 functioned as an endogenous sponge for miR-181a in mesangial cells (MCs) via direct targeting and in an Ago2-dependent manner. MiR-181a inhibition promoted MC fibrosis and inflammatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 37 publications
(39 reference statements)
3
73
0
Order By: Relevance
“…Studies have also begun to demonstrate the participation and regulatory mechanism of non-coding rnas (ncrnas) on dn development (6,7). circular rnas (circrnas) are a novel class of endogenous ncrnas, which mediate diverse physiological and pathological changes in the human body (8), including dn, and are characterized by a covalently-closed loop formed by back-splicing between the 5' to 3' ends of the polya tail (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also begun to demonstrate the participation and regulatory mechanism of non-coding rnas (ncrnas) on dn development (6,7). circular rnas (circrnas) are a novel class of endogenous ncrnas, which mediate diverse physiological and pathological changes in the human body (8), including dn, and are characterized by a covalently-closed loop formed by back-splicing between the 5' to 3' ends of the polya tail (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 For instance, lnc-MEG3 enhance inflammatory response via upregulating the expressions of early growth response protein 1 and Toll-like receptor 4. 5 Another study illuminates that overexpression of lnc-MEG3 upregulates the creatine kinase and lactate dehydrogenase activities, inducing cell apoptosis and myocardial ischemia-reperfusion injury. 6 Furthermore, it is reported that lnc-MEG3 acts as a molecular sponge for several microRNAs such as microRNA (miR)-21, miR-181a, and miR-7-5p to inhibit their downstream signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, it is reported that lnc-MEG3 acts as a molecular sponge for several microRNAs such as microRNA (miR)-21, miR-181a, and miR-7-5p to inhibit their downstream signaling pathways. 5,7,8 Among these target miRNAs, miR-21 functions as an important contributor for preventing inflammation and organ dysfunctions such as liver, kidney, and lung in sepsis. [9][10][11] Based on these previous studies, we hypothesized that lnc-MEG3 might be involved in the development and progression of sepsis via interacting with miR-21.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation of lncRNA MEG3 with abdominal infection (A), respiratory infection (B), skin and soft tissue infection (C), blood steam infection (D), and CNS infection (E) in sepsis patients. LncRNA MEG3, long non-coding RNA maternally expressed gene 3; CNS, central nervous system sepsis, thereby, lncRNA MEG3 was elevated in sepsis patients compared with HCs 20. Second, lncRNA MEG3 probably mediated cell apoptosis in major organs including kidney and heart, which subsequently accelerated multiple organ injury in sepsis, thereby, lncRNA MEG3 discriminated sepsis patients from HCs 15.…”
mentioning
confidence: 99%